Description of the Application of the I-O Method Approach in the Defense Sector through Modification of the Social Accounting Matrix (SAM) Model - Endro Tri Susdarwono (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2022)
This study applies a descriptive approach, the approach in question aims to provide an explanation or description of the application of the I-O method in the defense sector through the modification of the Social Accounting Matrix (SAM) Model, while the type of research applied in this study is descriptive qualitative research, namely interpreting or describing about everything that exists and is related, this interpretation relates to existing relationships or conditions, the process of an ongoing situation, effects or consequences that occur, opinions that are developing, or trends that are growing. In the Input–Output Method, the basic table is a transaction table consisting of: input coefficient table (coefficient matrix), multiplier table, attractiveness index table and driving force index as well as supporting tables and other analysis tables depending on the breadth of the field to be discussed. This study concludes that the I-O model is applied to the defense sector by developing the SAM (Social Accounting Matrix) model. This model is an extension of the I-O model which includes economic sub-sectors or more detailed sub-sectors.